Factors associated with utilization of Visual Inspection with Acetic Acid in Nepal - Tara Ramtel; Kamaliah Mohamad Noh; Prof. Dr. Narbada Thapa; Prof. Dr Krishna Gopal Rampal (International Journal of Public Health Science (IJPHS), 2022)
Visual inspection with acetic acid (VIA) is an optional cervical cancer screening method. National guideline of Nepal has emphasized using the VIA and intended to achieve at least a 50% screening rate by 2015 but the overall coverage is only 2.4% in 2019. A cross-sectional study was conducted to identify the factors associated with the utilization of VIA screening in Bagmati Province, Nepal. A convenience sample of 400 women aged 30 to 60 years were included in the study.   A semi-structured questionnaire was used to elicit information on VIA test and factors associated with it. Awareness, economic status, socio-psychological beliefs, service availability and accessibility, perception on service providers’ performance were associated with low VIA use in the province. VIA screening was associated with socio-demographic variables (χ2=29.9; df=4; p= <0.001), knowledge factors (χ2=69.29; df=3; p= <0.001) and with the perception on service providers’ performance (χ2=433.82; df=6; p= <0.001). Service providers’ approach during the VIA screening mattered on the acceptance of this service. The disparity was observed in the knowledge of cervical cancer and screening by the women. Based on this,there is a need for massive improvement  on the awareness of the community about the cervical disease and screening services.